Seasonal variations in plasma cortisol, testosterone, progesterone and leukocyte profiles in a wild population of tuco-tucos - Vera, Federico (2013)
Studies addressing seasonal changes in hormone levels are important in order to understand the interplays between ecology and physiology. In this study, we evaluated seasonal variations in cortisol, testosterone, and progesterone plasma levels in males and females of the subterranean rodent Ctenomys talarum. For the case of females, we also aimed to evaluate their capacity to increase their plasma cortisol concentrations in response to capture and restraint during reproductive and non-reproductive seasons. In addition, we registered concomitant seasonal variations in the neutrophil to lymphocyte ratio (N:L) aimed to discriminate between basal and stress-induced seasonal changes in cortisol levels in both males and females. Both basal and stressed-induced cortisol levels were significantly higher in reproductive than non-reproductive females. For the case of males, cortisol levels were also higher during the reproductive season, though values were two- to threefold lower than in females. The N:L ratios attained low values, typical of unstressed animals, in both males and females, indicating that the animals were not facing acute or chronic stressors at the moment of their capture. Testosterone levels in males were significantly elevated in relation to other mammals reaching up to 486 ng mL-1, with significantly higher levels during the reproductive season (mean: 209.45 177.76 ng mL-1) and a remarkable inter-individual variation. On the other hand, progesterone levels in females captured during reproductive and non-reproductive seasons were not significantly different. This study shows that seasonal modulation in testosterone and also in baseline and stress-induced cortisol levels occurs in tuco-tucos associated with reproduction.